Sex-Specific Cardiovascular Risks and Mortality in Patients with Panhypopituitarism: A Nationwide Cohort Study - Seung Shin Park; Hyunmook Jeong; Chang Ho Ahn; Min Jeong Park; Yong Hwy Kim; Kwangsoo Kim; Jung Hee Kim (Endocrinology and Metabolism)
Background Panhypopituitarism is a condition of combined deficiency of multiple pituitary hormones, which requires lifelong hormone replacement therapy. Hormone deficiency or inadequate hormone replacement may contribute to cardiovascular disease. Here, we aimed to investigate the burden of cardiovascular, cerebrovascular diseases and mortality in patients with panhypopituitarism. Methods A total of 5,714 patients with panhypopituitarism were enrolled in the Korean National Health Insurance Service database from 2003 to 2020. Panhypopituitarism was defined according to the International Classification of Diseases, 10th Revision (ICD- 10) codes for hypopituitarism, pituitary adenoma, or craniopharyngioma and the continuous prescription of thyroid hormone and glucocorticoids. The risks of all-cause mortality, coronary artery disease (CAD), heart failure (HF), ischemic stroke, and intracranial hemorrhage were compared between patients with panhypopituitarism and age-, sex-, and index year-matched controls. Results The mean age of patients with panhypopituitarism and matched controls was 55.1 years, and men accounted for 51.5%. Patients with panhypopituitarism showed significantly higher all-cause mortality compared to matched controls after adjustment for covariates (hazard ratio [HR], 2.18; 95% confidence interval [CI], 1.95 to 2.43 in men and HR, 3.09; 95% CI, 2.78 to 3.44 in women). Additionally, there were higher risks of CAD, HF, ischemic stroke, and intracranial hemorrhage in both sexes, except for CAD in men. Conclusion Patients with panhypopituitarism have elevated risks of cardiovascular and cerebrovascular diseases as well as increased mortality. These risks are particularly prominent for all-cause mortality in women. Therefore, proactive monitoring for cardiovascular and cerebrovascular complications is required in patients with panhypopituitarism.